Finite element modelling of a Piezoelectric beam and comparative performance study of Piezoelectric materials for voltage generation - Nechibvute, Action; Chawanda, Albert; Luhanga, P (Hindawi Publishing Corporation, 2014)
A comparative study of the traditional PZT ceramics and new single crystals is critical in selecting the best material and optimization of transducer design for applications such as conversion of ambient vibrations into useful electrical energy. However, due to material and fabrication costs, and the need for rapid prototyping while optimizing transducer design, primary comparisons can be based on simulation. In this paper, the COMSOL Multiphysics finite element package was used to study the direct piezoelectric effect when an external load is applied at the free end of a piezoelectric composite beam. The primary output parameters such as electric potential and electric field where studied as a function of the input strain and stress. The modeling is presented for the relatively new single crystal lead magnesium niobate-lead titanate (PMN32) and three different lead zirconate titanate ceramics (PZT-5A, PZT-5H, PZT-4). Material performance was assessed by using a common geometry and identical excitation conditions for the different piezoelectric materials. For each material, there are three analyses performed, namely static, eigenfrequency and transient/time dependent analysis. Comparative results clearly suggest that the new crystal material PMN32 is capable of outperforming presently used piezoelectric ceramics for voltage generation